The bilobed arterialized venous free flap for simultaneous coverage of 2 separate defects of a digit - Hyza, Petr; Vesely, Jiri; Stupka, Igor; Cigna, Emanuele; Monni, Nicola (Annals of plastic surgery, 2005)
We report a case of a 17-year-old patient who sustained multiple finger contusions on the left hand. After thorough debridement, the volar and dorsal defects of the middle finger were covered simultaneously with bilobed arterialized venous free flap from the left forearm. The flap was composed of 2 paddles, which were connected by a subcutaneous bridge containing a subcutaneous venous network. The subdermal plexus in the bridge was interrupted with no impairment of blood supply to the second cutaneous paddle. The flap survived completely with only temporary mild venous congestion. Excellent functional and cosmetic result was reached. We consider bilobed arterialized venous free flap as a useful option for coverage of concomitant volar and dorsal digital defects.
Keywords: chirurgické laloky; mikrochirurgie; poranění prstů ruky; ženské pohlaví; Surgical Flaps; Debridement; Finger Injuries; Humans; debridement; zákroky plastické chirurgie; Female; Adolescent; Microsurgery; lidé; Plastic Surgery Procedures; mladiství